The Depiction Of Magical Objects In English And Uzbek Fairy Tales - Safarova, Zilola Tolibovna; Temurova, Dilorom (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
It is widely known that magical objects constitute core narrative and symbolic parts of folk tales. Through the analysis of English and Uzbek fairy tales it has been proved that such objects not only help develop the plot of the narrative but also illustrate national culture, moral values and religious beliefs of people. The following article investigates the depiction and artistic functions of magical images in English and Uzbek folk tales. Through the comparative literary analysis of fairy tales and textual examples, the article reveals that magical objects used in English and Uzbek folklore share common literary functions, though their forms and meanings have been shaped in different cultural contexts.